Digital marketing and customer orientation as predictors of sustainability in tourism SMES - Nancy Tupac Yupanqui Lima; Karla Liliana Haro-Zea; Robin Alexander Díaz Saavedra (Innovative Marketing, 2024)
Digitalization in the business world is one of the crucial milestones that has generated great expectations and levels of importance in different business sectors, which is why this study aimed to analyze the influence of digital marketing and customer orientation on the sustainability of tourism small and medium-sized enterprises (SMEs) in Cusco, Peru. For the generation of the items, an evaluation of the sufficiency, coherence, clarity, and relevance was made by means of an expert panel of five professionals and five academics from the area of marketing and sustainability from three countries (Colombia, Peru, and Mexico), who have more than 20 years of experience. The fieldwork was carried out through convenience sampling with 516 companies in the tourism sector. The data were collected through a survey online in Google Forms, distributed through social networks: WhatsApp, Instagram, Facebook, LinkedIn, and email in Cusco, Peru, during July and August 2022. The confirmatory analysis was performed. In the theoretical model analysis, an adequate fit was obtained, 2 = 303.74, p < .001, IFC = .934, RMSEA = .078, SRMR = .054, with an appropriate internal consistency (digital marketing α = 0.95, customer orientation α = 0.96, sustainability α = 0.90).